Effect of Moisture Stress on Various Seedling Emergence in Medium Black Soils of Kota - Tyagi, S.C.; Sharma, D.L.; Tomar, S.P. (Journal of Soil and Water Conservation, 2022)
A laboratory experiment was conducted to find the optimum soil moisture levels for germination of seeds of seven major crops grown in medium black soils of Kota District. viz. wheat, barley, gram lentil, peas, safflower and sunflower. Cereals showed maximum germination at 2450m. bar moisture tension in black soils. The higher and the lower soil moisture tensions have decreased the germination percentage. Gram and lentil had maximum germination at 1550m. bar moisture tcnsion whereas peas at 97-70m. bar. The oil seed crops safflower and sunflower germinated to maximum extent at 2450m. bar although these showed appreciable germination at 9770m. bar. Seed germination was relatively slower at higher moisture tension. An adequate plant stand is a must for obtaining optimum yield of a crop. Seeds of different crops have different moisture requirements for germination, some seed species can germinate & easily establish under limited soil moisture where as the others need higher soil moisture to germinate. Germination of some species is completely prohibited at a certain level by moisture stress whereas, others have the ability to germinate over the entire limits of moisture stress from field capacity to permanent wil- ting point (Doneen and Hacgillivary (1943), Hunter and Eriokson (1952) and Bellch (1970), Owen (1952) reported that only 20 percent of the wheat seeds germinated at a moisture content less than permanent wilting point. Arca and Garcia (1963) reported that germination of maize seeds was unaffected by soil moisture contents from 10.8 to 16.8 percent. A gradual reduction in germination percentage and seedline vigor due to increased osmotic tension was reported by Younis et al. (1963), Fanous (1967) and Ballch (1970). The present study was conducted to evaluate the relative sensitivity of different rabi seeds to various moisture levels during germi- nation.